Seasonal Patterns in Incidence and Antimicrobial Resistance of Common Bacterial Pathogens in Nursing Home Patients and Their Rooms - Cassone, Marco; Mantey, Julia; Gontjes, Kyle J.; Lansing, Bonnie J.; Gibson, Kristen E.; Wang, Joyce; Mody, Lona (Frontiers in Public Health, 2021)
Background: Colonization is the main precursor to infection, which may lead to adverse clinical outcomes among older adults in Nursing Homes. Understanding seasonal changes in the local burden of common bacterial pathogens is key to implement appropriate and cost-effective infection prevention measures in this resource-constrained healthcare environment. It is thus surprising that seasonal trends in patient and environmental colonization with major bacterial pathogens are presently unknown in the expanding setting of Nursing Homes. Methods: We examined the seasonal incidence of four major pathogens among Nursing Home patients and high-touch surfaces within their rooms over two years. In cases where a significant number of antimicrobial-resistant strains was found, incidence in antimicrobial-susceptible and antimicrobial-resistant isolates was compared, along with antibiotic use trends. Results: We observed spring peaks in the incidence of vancomycin-resistant enterococci (1.70 peak to trough ratio for both patient and environmental isolates) and methicillin-resistant Staphylococcus aureus (1.95 peak to trough ratio for patient isolates, 1.50 for environmental isolates). We also observed summer peaks in Klebsiella pneumoniae (1.83 and 1.82 peak to trough ratio for patient and environmental isolates, respectively) and ciprofloxacin-resistant Escherichia coli. Susceptible S. aureus and E. coli did not follow seasonal patterns. Conclusions: A meaningful seasonal pattern may be present in the NH setting for several significant pathogens, and especially antimicrobial-resistant ones. Whether such patterns are consistent across geographic areas and over longer periods of time should be a key focus of investigation, in order to better inform timing of surveillance and infection prevention efforts in Nursing Homes.